Contribution of celiac disease autoantibodies to the disease process. (February 2012) - Lindfors, Katri; Kaukinen, Katri
Evaluation of: Teesalu K, Panarina M, Uibo O, Uibo R, Utt M. Autoantibodies from patients with celiac disease inhibit transglutaminase 2 binding to heparin/heparan sulfate and interfere with intestinal epithelial adhesion. Amino Acids doi:10.1007/s00726-011-1020-1 (2011) (Epub ahead of print). Transglutaminase 2 is a multifunctional protein involved in cellular adhesion. Moreover, transglutaminase 2 has been identified as the autoantigen in celiac disease, and in untreated celiac disease, in addition to being present in the serum, the transglutaminase 2-targeted autoantibodies are bound to their antigen in the basement membrane underlining the small-bowel mucosal epithelium. Furthermore, the disease-specific transglutaminase 2-targeted autoantibodies have been experimentally shown to exert various biological effects on different cell types. Using Caco-2 intestinal epithelial cells, it has now also been demonstrated that serum transglutaminase 2-targeted autoantibodies from untreated celiac patients inhibit the adhesion of these cells. These findings provide an important direction for future research to improve our general understanding of celiac disease pathogenesis and especially the role of the disease-specific autoantibodies during the progression of the disorder.